Immunization of neonates with trivalent oral poliomyelitis vaccine (Sabin) - De-xiang, Dong (1986)
A study was carried out between November 1981 and April 1982 on the immunological effect of administering trivalent live, oral polio vaccine to 200 mature healthy neonates from Henan Province, China. The initial dose of vaccine was given at 3 days of age, and 2 months thereafter antibodies to poliovirus types 1, 2, and 3, respectively, were detected in 46.7%, 60.7% and 48.6% of the neonates; after the second dose, the levels were 86.9%, 95.3%, and 97.2%, with geometric mean titres of 1:106.2, 1:349.8, and 1:232.5. Almost 100% of neonates exhibited antibodies after the fourth dose of vaccine. Eighty-two percent of the neonates excreted poliovirus for at least a week after the initial dose of vaccine, and this increased to 99% after the second dose. Seroconversion at 4 months of age was similar to that of a group of controls who received their initial dose of vaccine at 2 months of age; however, immunization of neonates induced immunity to poliovirus at the earliest possible age.